2020
DOI: 10.1093/cid/ciaa754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Water, Sanitation, and Hygiene Mobile Health Program on Diarrhea and Child Growth in Bangladesh: A Cluster-randomized Controlled Trial of the Cholera Hospital-based Intervention for 7 Days (CHoBI7) Mobile Health Program

Abstract: Background The Cholera-Hospital-Based-Intervention-for-7-days (CHoBI7) mobile health (mHealth) program was a cluster-randomized controlled trial of diarrhea patient households conducted in Dhaka, Bangladesh. Methods Patients were block-randomized to three arms: standard recommendation on oral rehydration solution use; health facility delivery of CHoBI7 plus mHealth (no home visits); and health facility delivery of CHoBI7 plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…41,42 A recent RCT of the CHoBI7 mHealth program resulted in significantly lower pediatric diarrhea and stunting as well as improved drinking water quality and handwashing with soap. 43 A prospective cohort study nested within this RCT investigated potential risk factors for growth faltering among children under 5 years of age, and found that children with caregiver reports of mouthing soil and children with animals in their sleeping space had a significant reduction in height-for-age Z-scores from baseline to the month 12 followup. 44 A second cohort study in this population assessed the association between soil-and object-to-mouth contacts and diarrhea prevalence for children under 5 years of age, and found that the odds of having a diarrhea episode in the subsequent month were significantly higher for children with caregiver reports of mouthing feces within the past week.…”
mentioning
confidence: 99%
“…41,42 A recent RCT of the CHoBI7 mHealth program resulted in significantly lower pediatric diarrhea and stunting as well as improved drinking water quality and handwashing with soap. 43 A prospective cohort study nested within this RCT investigated potential risk factors for growth faltering among children under 5 years of age, and found that children with caregiver reports of mouthing soil and children with animals in their sleeping space had a significant reduction in height-for-age Z-scores from baseline to the month 12 followup. 44 A second cohort study in this population assessed the association between soil-and object-to-mouth contacts and diarrhea prevalence for children under 5 years of age, and found that the odds of having a diarrhea episode in the subsequent month were significantly higher for children with caregiver reports of mouthing feces within the past week.…”
mentioning
confidence: 99%
“…The eligibility criteria for CHoBI7 mHealth RCT participants interviews is reported elsewhere. 35,37 Neighbors were eligible to participate in an interview if they had a child younger than 5 years in the home. Interviews followed a guide that covered the following topics: types of food consumed by young children, food storage and reheating practices, caregivers' experiences with child mouthing of dirt or dirty objects, child toileting practices, child feces disposal practices, male household member involvement in child and household activities, and preferences for mHealth message delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-four households were in an intervention arm of the CHoBI7 mHealth RCT and had previously received weekly mobile messages on handwashing with soap and water treatment for 12 months in addition to WASH-enabling technology (a handwashing station and water vessel with lid and tap) and an in-person visit for delivery of a pictorial module; 16 households were in the standard message arm and had received no prior WASH intervention. 35,37 All pilot phase 1 households received at least bi-weekly voice and text messages for up to 3 months from the Baby WASH mHealth program.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations